Abundance, Diversity and Distribution of Macrobenthic Mollusks in Reef flats of Taklong Island National Marine Reserve (TINMR), Guimaras - Espeja, Christine Anne D.
Mollusks are important as they serve as transitional organisms and good indicator of reef health. This study determined the current status of the macrobenthic molluscs of the three (3) reef flats in Taklong Isaland National Marine Reserve, Guimaras. Ecological properties of macrobenthic mollusk communities e.g. diversity, dominant species, density and distribution were computed based on three 100m2 belt transects established per site. Coral cover (and of other life forms), a determinant of reef health were these mollusks live, was computed based on line intercept method. Mollusk communities in the 3 reef flat sites were highly diverse (H? = 2.36-3.17) but with low similarity (Jaccard coeff., J = 0.38-0.42). A total of 109 species belonging to 35 families were recorded of which 54 live species, 16 species comprised 80% of total live population. Calaparan was the most species-rich site (s=35) followed by Talisay (s=30) and least was Kalirohan (s=29). Dominant species varied and may be influenced by habitat structure i.e. Coralliophila neritoidea, a corallivore, was most dense (0.03 ind m¬¬¬¬-2) in Talisay which had the highest live coral cover (50%); the herbivore, Pyrene scripta was most dense (D=0.06 ind. m-2¬¬) in Calaparan with high algal cover (41%) and the carnivore Conus sp. was very abundant (D=0.19 ind. m-2) in Kalirohan with high % of dead coral with algae (51%).